Challenges of Technology Integration in Teacher Education Programmes in Bangladeshi Tertiary Institutions - Hossain, Ghazi Shahadat (English Language Teaching Perspectives, 2023)
Technology integration has considerably affected teaching and learning cultures and resulted in revolutionary changes to worldwide pedagogical practices. For numerous reasons, including a lack of experience, policy, planning, infrastructure, and the environment, many educational institutions have not been able to gain the greatest benefits from technology. This study, seen through the lens of Activity Theory, reports the challenges of technology integration in the teacher education programs of tertiary institutions of Bangladesh. It has employed an interpretative qualitative research design for data elicitation and data analysis. Seven written reflection papers on the barriers of technology integration from both male and female teacher educators working in various private public universities were collected. The findings reveal that a variety of issues such as lack of tech-tools, devices, training and related expertise, administrative support, electricity, technology-equipped classrooms, attitudes of teachers and students, gap between theory and practice hinder teacher educators’ effective integration of technology in pedagogical practice of teacher education programs in Bangladesh. The findings can have implications for policy makers, curriculum designers, and other stakeholders with similar or different educational contexts.